Biophysical studies in polymer therapeutics: the interactions of anionic and cationic PAMAM dendrimers with lipid monolayers. (26th November 2017) - Wilde, Marleen; Green, Rebecca J.; Sanders, Michael R.; Greco, Francesca
Abstract: Understanding how polymers interact with biological membranes is important for the development of polymer-based therapeutics and wider biomedical applications. Here, biophysical methods (surface pressure measurements, external reflection FTIR) have been used to investigate the interaction between PAMAM dendrimers (Generation 5 or 4.5) and anionic (DPPG) or zwitterionic (DPPC) model membranes. We observed a concentration-dependent binding behaviour of both PAMAM species to both model membranes; however, equivalent levels of penetration into DPPC monolayers required approximately 10-fold higher dendrimer concentrations than for penetration into DPPG monolayers. Overall, the anionic PAMAM G4.5 showed a slightly better penetration ability which could be caused by repulsive forces towards the lipid layers. In comparison, increasing concentration of cationic PAMAM G5 leads to saturation of adsorption at the anionic lipid surface before penetration into the lipid layer likely driven by electrostatic attraction. Our studies also showed that physiologically relevant concentrations of sodium chloride (144 mM) decreased PAMAM penetration into DPPG monolayers but did not significantly affect the dendrimer–DPPC interaction. These results provide an insight into the mechanism of interaction between charged dendritic polymers with a lipid interface and show that the nature of such interactions are affected by lipid headgroup, dendrimer charge and solution salinity.